The execution order of the concurrent training and its effects on static and dynamic balance, and muscle strength of elderly people - Juliana Cristina Silva; Eduardo Martins Brandão; Guilherme Morais Puga; Ana Carolina Kanitz (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: Assess the effect of the performance order in the Concurrent Training (CT), Aerobic-Strength (AS), and Strength-Aerobic (SA), in the static balance, dynamic balance, and muscle strength in elderly people. Methods: The study involved 38 elderly people (men and women) aged 60 to 75 years old, divided into SA (n = 19) and AS (n = 19). Within 12 weeks, the aerobic training consisted of walking with intensity prescribed by the Borg's Rating of Perceived Exertion (6-20) and the strength training consisted of six exercises, with intensity controlled by Repetition Maximum training zones. Static balance (plantar pressure center area and displacement in bipedal support with eyes closed and open), dynamic balance (Timed Up and Go and Tandem Gait), and maximum dynamic strength of knee extension and bench press have been evaluated. For data analysis, Generalized Estimating Equations with Bonferroni's complimentary test have been used (α = 0.05). Results: For static and dynamic balance there hasn't been an effect on the 12 weeks of combined training, regardless of the performance order. Both groups maintained the balance variables within the intervention period. When it comes to strength, there has been a noticeable improvement in lower limbs (SA: 16%; AS: 11%; p < 0,001) and upper (SA: 22.0%; AS: 8.7%; p < 0.001), without any differences between the groups. Conclusion: So there is no difference between the order of performance of the CT in the variables of static and dynamic balance and strength of upper and lower limbs. Furthermore, after training, there have been significant improvements in the variables of strength and maintenance of static and dynamic balance.